Understanding the role of "sunshine vitamin D" in Parkinson's disease: A review - Tapan Behl; Arpita Arora; Rajeev K. Singla; Rajeev K. Singla; Aayush Sehgal; Hafiz A. Makeen; Mohammed Albratty; Abdulkarim M. Meraya; Asim Najmi; Simona Gabriela Bungau; Simona Gabriela Bungau (Frontiers Media S.A., 2022)
Next to Alzheimer's disease, Parkinson's disease constitutes the second most widespread neurological disorder, primarily affecting the older population. Its symptoms are noticeable with advancing age including tremors, postural imbalance, and slow movements, and over time, these symptoms get aggravated, progressing to osteoporosis, osteopenia, and risk of fractures. These symptoms correlate to low bone density and hence weakened bones; thus, vitamin D proves to be an intricate component of the pathogenesis of the disease. Moreover, lower serum concentrations of vitamin D have been found in diseased subjects. Supplementation with vitamin D can retard the aggravation of non-motor as well as motor symptoms of Parkinson's disease that include cognitive improvement along with the decline in risk of fractures. Also, vitamin D is extremely crucial for brain functioning, targeting dopaminergic neurons, and almost the entire functioning of the brain is affected. However, further exploration is required to determine the toxic dose of vitamin D in Parkinson's subjects. This "sunshine vitamin" surely can be a ray of sunshine for neurologically diseased subjects.